2018
DOI: 10.1002/jum.14893
|View full text |Cite
|
Sign up to set email alerts
|

Role of Virtual Touch Tissue Imaging Quantification in the Assessment of Hepatic Sinusoidal Obstruction Syndrome in a Rat Model

Abstract: Objectives To investigate the value of liver stiffness in rats with various degrees of hepatic sinusoidal obstruction syndrome (HSOS) induced by monocrotaline by comparing liver histopathologic findings. Methods Seventy rats were randomly divided into a control group (n = 10), a low‐dose monocrotaline group (n = 30), and a high‐dose monocrotaline group (n = 30). After successful modeling, the liver shear wave velocity (SWV) by Virtual Touch tissue imaging quantification (Siemens Medical Solutions, Mountain Vie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Importantly, stiffness measurements were below that which would be considered as fibrosis in rats (Hu et al, 2015;Hu et al, 2017), in line with the absence of fibrosis in previous histological studies of the alcoholfeeding model (Diehl, et al, 1990;Koniaris et al, 2003;Juskeviciute et al, 2016). However, we report increases in liver stiffness similar to what has been shown in a rat model of hepatic sinusoidal obstruction syndrome (Han et al, 2019), as well as human transplant donors who underwent a liver resection (Ninomiya et al, 2011). Additionally, extracellular matrix rebuilding could contribute to elevated stiffness, but only at later time points (72 h post-PHx) when this rebuilding is thought to occur (Michalopoulos, 2010;Juskeviciute et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, stiffness measurements were below that which would be considered as fibrosis in rats (Hu et al, 2015;Hu et al, 2017), in line with the absence of fibrosis in previous histological studies of the alcoholfeeding model (Diehl, et al, 1990;Koniaris et al, 2003;Juskeviciute et al, 2016). However, we report increases in liver stiffness similar to what has been shown in a rat model of hepatic sinusoidal obstruction syndrome (Han et al, 2019), as well as human transplant donors who underwent a liver resection (Ninomiya et al, 2011). Additionally, extracellular matrix rebuilding could contribute to elevated stiffness, but only at later time points (72 h post-PHx) when this rebuilding is thought to occur (Michalopoulos, 2010;Juskeviciute et al, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…However, the exact mechanism of this treatment modality is unclear. Previous studies have suggested that acute portal hypertension is an important pathophysiological feature of PA-HSOS, which is caused by an increase in resistance in the blood sinus 13,14 . Anticoagulation -TIPS stepwise therapy can reduce portal pressure by establishing a shunt, thereby achieving a therapeutic effect.…”
Section: Introductionmentioning
confidence: 99%